Difficulties in learning reading and writing in children with apraxia of speech - Simić, Ljiljana (Norma, 2022)
Mastering the skills of reading and writing encourages intensive lexical development that enriches the ability to speak and write. The presence of a delay or an identified speech and/or language disorder at an early age affects the outcome of learning these skills. The aim of this paper is to familiarize readers with the characteristics of apraxia of speech and to draw attention to the difficulties these children exhibit in the process of learning to read and write. Apraxia of speech represents a difficulty in planning and programming the position of the speech organs that are required for the production of speech sounds. For a long time it was believed that this was exclusively a motor speech disorder. New findings changed the aspect of observing this disorder where language disorders were also identified in these children. The primary reason for children with apraxia of speech having difficulty acquiring reading and writing is a delay in the development of phonological awareness, which is known to be the basis of the language system for learning academic skills. Research dealing with the characteristics of written language in children with apraxia of speech is scarce, especially in the Serbian language. A review of the available literature found an emphasis on the presence of language barriers that are assumed to hinder the acquisition of these skills, which subsequently results in poorer academic performance.